2016
DOI: 10.1177/1078155215603231
|View full text |Cite
|
Sign up to set email alerts
|

Use of vemurafenib in a patient unable to swallow whole

Abstract: The treatment landscape for metastatic melanoma has increased dramatically in the past five years, with the pivotal discovery of activating BRAF mutations in half of all melanomas spurring the development for effective treatments that target mitogen-activated protein kinase (RAS/RAF/MEK/ERK) pathway. Vemurafenib, a selective mutant BRAF Val600 inhibitor, results in striking tumour responses and a survival advantage over conventional chemotherapy. We present here the case of a 38-year-old woman with metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…In both cases, patients had a partial response and a significant benefit of short duration. 6,7 Compared to our patients, there was no difference in efficacy and tolerance of this altered administration of treatment. Even if the efficacy of treatment was short-lived, patients and family appreciated our having tried to provide the best care.…”
Section: Discussioncontrasting
confidence: 62%
“…In both cases, patients had a partial response and a significant benefit of short duration. 6,7 Compared to our patients, there was no difference in efficacy and tolerance of this altered administration of treatment. Even if the efficacy of treatment was short-lived, patients and family appreciated our having tried to provide the best care.…”
Section: Discussioncontrasting
confidence: 62%
“…Review of agents found 36 (31%) with guidance for alternative routes of administration readily available in tertiary resources or commercial liquid formulations, 38 (33%) with off‐label manufacturer information or case reports describing manipulation of solid dosage formulations, and 42 (36%) with no data or insight limited to pharmacokinetic studies. Findings are detailed in Table 3 10‐196 . Unique administration instructions (ie, with or without foo...…”
Section: Resultsmentioning
confidence: 99%